1998
DOI: 10.1016/s0735-1097(98)00387-8
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of electron beam computed tomography scanning for distinguishing ischemic from nonischemic cardiomyopathy

Abstract: This prospective, blinded study indicates that EBCT detected CC accurately and can noninvasively distinguish between cardiomyopathy because of CAD and nonischemic causes of left ventricular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 34 publications
1
35
0
1
Order By: Relevance
“…One large study of 120 patients with heart failure of unknown etiology demonstrated that the presence of CACP was associated with 99% sensitivity for ischemic cardiomyopathy. 93 Another study demonstrated similarly high sensitivity using dual CT to differentiate ischemic from nonischemic cardiomyopathy. 94 Direct comparison studies have demonstrated this methodology to be more accurate than echocardiography and MPS techniques.…”
Section: Ct Coronary Calcium and Symptomatic Patientsmentioning
confidence: 93%
“…One large study of 120 patients with heart failure of unknown etiology demonstrated that the presence of CACP was associated with 99% sensitivity for ischemic cardiomyopathy. 93 Another study demonstrated similarly high sensitivity using dual CT to differentiate ischemic from nonischemic cardiomyopathy. 94 Direct comparison studies have demonstrated this methodology to be more accurate than echocardiography and MPS techniques.…”
Section: Ct Coronary Calcium and Symptomatic Patientsmentioning
confidence: 93%
“…Asymptomatic patients without CAC are considered to be low risk, and coronary CT angiography is not recommend in this group 34) . It has also been reported that the CAC score positively correlates with the number of coronary vessels affected by CAD, even in patients with proven CAD 35) , while an elevated CAC score is associated with higher morbidity and mortality rates 36) . Nevertheless, the general use of CAC scoring may be limited, as the high prevalence of CAC results in low specificity for obstructive CAD in symptomatic patients 37) .…”
Section: Cac Score and Cardiovascular Morbidity And Mortality In The mentioning
confidence: 96%
“…Multiple studies have shown the value of CAC scores in excluding CAD as the etiology for heart failure (20)(21)(22). In patients with a diagnosis of heart failure, an Agatston score of 0 has been shown to have 100% specificity in excluding "high-risk CAD," defined as left main coronary artery stenosis or stenosis in at least 2 major epicardial coronary arteries (20,22).…”
Section: Ischemic Versus Nonischemic Cardiomyopathymentioning
confidence: 99%